Sustainable entrepreneurial ecosystems: what are the main schools of thought and topical trends? - Truong Thi Thuy Ninh; Truong Thi Hue (Discover Sustainability)
Abstract Today, sustainability challenges are significant and cannot be addressed in isolation. Consequently, in entrepreneurship research, scholars focus on sustainable entrepreneurial ecosystems (SEEs), where various agents interact and support each other in addressing sustainability issues. However, SEE is still an emerging field, with research occurring only in its early stages; rather, it has been primarily theoretical and fragmented. This study aims to conduct a bibliometric review of the literature on SEE. A total of 102 documents indexed in Scopus from 2004 to 2023 were evaluated for validity and included in the bibliometric analysis. It reveals the volume, growth trajectory, document types, geographic and international contributions, influential authors, prominent documents, main schools of thought, and topical trends in the SEE literature. The findings indicate that research on SEE has significantly increased since 2021. A total of 49 countries have contributed to this field, with the most prolific being the United States, the United Kingdom, and Germany. The following four main schools of thought are revealed: (1) developing SEE through digital technologies, moral values, and education; (2) theory, practice, and implications of SEE; (3) comparative insights and empirical perspectives on SEE; and (4) mapping SEE and addressing social collaboration challenges for sustainable outcomes. Four topic trends and several future research directions have also been identified. This is one of the few studies aimed at reviewing SEE, and it is likely the first to use Scopus data updated through 2023. This paper makes substantial contributions to the SEE domain, promoting further research aligned with sustainable development goals. Clinical trial number: Not applicable.